Natural language markers of social phenotype in girls with autism. (10th November 2020) - Song, Amber; Cola, Meredith; Plate, Samantha; Petrulla, Victoria; Yankowitz, Lisa; Pandey, Juhi; Schultz, Robert T.; Parish‐Morris, Julia
Abstract : Background: Girls with autism spectrum condition (ASC) are chronically underdiagnosed compared to boys, which may be due to poorly understood sex differences in a variety of domains, including social interest and motivation. In this study, we use natural language processing to identify objective markers of social phenotype that are easily obtained from a brief conversation with a nonexpert. Methods: 87 school‐aged children and adolescents with ASC (17 girls, 33 boys) or typical development (TD; 15 girls, 22 boys) were matched on age (mean = 11.35 years), IQ estimates (mean = 107), and – for ASC participants – level of social impairment. Participants engaged in an informal 5‐min 'get to know you' conversation with a nonexpert conversation partner. To measure attention to social groups, we analyzed first‐person plural pronoun variants (e.g., 'we' and 'us') and third‐person plural pronoun variants (e.g., 'they' and 'them'). Results: Consistent with prior research suggesting greater social motivation in autistic girls, autistic girls talked more about social groups than did ASC boys. Compared to TD girls, autistic girls demonstrated atypically heightened discussion of groups they were not a part of ('they', 'them'), indicating potential awareness of social exclusion. Pronoun use predicted individual differences in the social phenotypes of autistic girls. Conclusions: Relatively heightened but atypical social group focus is evident in autistic girls during spontaneous conversation, which contrasts with patterns observed in autistic boys and TD girls. Quantifying subtle linguistic differences in verbally fluent autistic girls is an important step toward improved identification and support for this understudied sector of the autism spectrum.